Sibling number and early interactions shape social competence for life - Bruno Camargo-dos-Santos; Barbara Taborsky (Proceedings of the National Academy of Sciences, 2026)
The social environment experienced during development plays a crucial role in shaping social competence—the ability to respond appropriately to social challenges. Sibling number and the social interactions between them are key components of the early lives in many animals. While these components are well known to influence social development in humans, their role in nonhuman animals remains unclear. Here, we show that both the number of siblings and opportunities for social interaction are essential for developing social competence in the highly social cichlid Neolamprologus pulcher . Fish reared in large broods (LB) displayed more affiliative and fewer aggressive or submissive behaviors during early life compared to those reared in small broods (SB) or in large broods with restricted opportunities for interactions (4 × 8). Later in life, LB fish were more socially competent. Thus, social competence arises not from the number of individuals or interactions alone, but from the combination of both.